Patients with Coronary Artery Disease Have Lower Levels of Antibody to Heat-Stressed Fibroblast Derived Proteins, versus Normal Subjects - Azin Aghamajidi; Hesam Babaei Khameneh; Narges Amirjamshidi; Seyed Farzad Jalali; Haleh Akhavan-Niaki; Soraya Khafri; Seyedeh Narges Mousavi; Monireh Golpour; Maryam Mehri; AmrollahMostafazadeh (Cardiovascular Therapeutics)
Cellular stress response plays an important role in the pathophysiology of coronary artery disease (CAD). Inhibition of cellular stress may provide a novel clinical approach regarding the diagnosis and treatment of CAD. Fibroblasts constitute 60-70% of cardiac cells and have a crucial role in cardiovascular function. Hence, the aim of this study was to show a potential therapeutic application of proteins derived from heat-stressed fibroblast in CAD patients. Fibroblasts were isolated from the foreskin and cultured under heat stress conditions. Surprisingly, 1.06% of the cells exhibited a necrotic death pattern. Furthermore, heat-stressed fibroblasts produced higher level of total proteins than control cells. In SDS-PAGE analysis, a 70 kDa protein band was observed in stressed cell culture supernatants which appeared as two acidic spots with close pI in the two-dimensional electrophoresis. To evaluate the immunogenic properties of fibroblast-derived heat shock proteins (HSPs), the serum immunoglobulin-G (IgG) was measured by ELISA in 50 CAD patients and 50 normal subjects who had been diagnosed through angiography. Interestingly, the level of anti-HSP antibody was significantly higher in non-CAD individuals in comparison with the patient’s group (p<0.05). The odds ratio for CAD was 5.06 (95%CI=2.15‐11.91) in cut-off value of 30 AU/mL of anti-HSP antibody. Moreover, ROC analysis showed that anti-HSP antibodies had a specificity of 74% and a sensitivity of 64%, which is almost equal to 66% sensitivity of exercise stress test (EST) as a CAD diagnostic method. These data revealed that fibroblast-derived HSPs are suitable for the diagnosis and management of CAD through antibody production.